SIKAP BAHASA MAHASISWA DAN DOSEN TERHADAP ISTILAH TERJEMAHAN DAN ISTILAH SERAPAN BIDANG EKONOMI HASIL MABBIM - Wiwiek Dwi Astuti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
This essay is a part of a research titled “Keberterimaan Istilah Mabbim Bidang Ekonomi di Kalangan Perguruan Tinggi”. If the aim of this research is to khow the attitude and the acceptance among student and lecturer toward Indonesian terms, whether it is translation or applied, this essay just report the attitude of student and lecturer toward Indonesian aterms, whether it is translation and loan word (serapan). There are two variables used in this research, free variable and bound variable. Free variable includes respondent social factors such as sex, mother-tongue background, age, educational degree, and the length of respondent involves in economic field. Meanwhile, boun variable in this research is athe tendency and the conviction or respondent attitude toward Indonesian terms. Mark is counted statistically based on T-Test and Anova-Test. Both statistic tests are used to measure the significance of attitude difference based on research variable.